KINERJA KEUANGAN PERUSAHAAN SAAT PANDEMI COVID-19 DALAM KAJIAN ISLAM (Studi Kasus: PT Surya Toto Indonesia Tbk.) - Muhammad Rafi Dhiaulhaq; Achmad Jufri; Darmawan (Jurnal Publikasi Ekonomi dan Akuntansi, 2023)
Assessment of financial ratios and the relationship between one item and another in the financial statements can provide an overview of the performance and level of financial soundness of a company. This article aims to assess the financial performance of PT. Surya Toto Indonesia Tbk. in 2019-2021 during the Covid-19 pandemic. The analysis was carried out using various financial ratios, namely profitability ratios, liquidity ratios, solvency ratios and activity ratios to see the company's performance from 2019 to 2021. The results showed the rate of return on net sales, return on equity, financial performance of PT. Surya Toto Indonesia Tbk is not good enough. Return on assets value current ratio in 3 consecutive years is 2 times, which means the company's profitability is good. In 2020 2 times, and PT. Surya Toto Total debt to total assets, interest coverage ratio, accounts receivable turnover ratio, inventory turnover ratio, Debt turnover where the financial performance is good.